Molecular Docking of Ferulic Acid Derivatives on P2Y12 Receptor and their ADMET Prediction - Juni Ekowati; Nuzul Wahyuning Diyah; Kholis Amalia Nofianti; Iwan Sahrial Hamid; Siswandono Siswandono (Institute for Research and Community Services (LPPM) ITB, 2018)
P2Y12 is a platelet receptor that is involved in ADP signal transduction and is an attractive target for antithrombotic drugs. The side effects of antithrombotic drugs are not pleasant for the patient, so research into the development of new antithrombotic agents is still necessary. Evaluation of absorption, distribution, metabolism, elimination, and the toxicity profile of candidate drugs is an important step in drug development. The aim of this study was to predict the potency of ferulic acid (FA) and its derivatives (FA1-24) as antiplatelet drugs by a docking study on the P2Y12 receptor (PDB ID: 4PXZ) and their ADMET performance. The docking study was performed using Molegro Virtual Docker, version 5.5. ADMET prediction of FA was conducted using the pkCSM online tool. The results of the in silico study showed that FA-19 had the lowest MolDock score (MDS), which means that this compound is predicted to have the greatest activity. FA-19 is also predicted to be practically non-toxic. It is expected that FA-19 will have good intestinal absorption and is similarly distributed in the intestine and in the blood plasma. Its penetration in the blood-brain barrier is moderate but does not inhibit the CYP2D6 and CYP3A4 enzymes.